Dynamics of an Eco-Epidemiological Model Consisting of Herding Prey and Harvested Predator - Mustafa, Arkan N. (Sulaimani Journal for Pure and Applied Sciences, 2019)
In this paper, the dynamics of predator-prey interaction, only at the outer surface of herd formed by prey population and spreading SI-disease in predator population, is modeled mathematically. The boundedness and persistence of our model are studied and local dynamical behaviors are investigated. Furthermore, the conditions that guarantee the occurring of Hopf-bifurcation of the model are established. Finally, we confirm our analytical findings with the help of numerical simulation
Keywords: Prey predator model; Herding prey; Functional responses; Stability analysis